Flouting Conversational Maxims by Connor Watts in Skiptrace: Pelanggaran Maksim Percakapan oleh Connor Watts dalam Skiptrace - Putri Anadewi AN putri; Vidya Mandarani (Academia Open, 2023)
Background conversational maxims play a crucial role in facilitating effective communication and understanding in dialogue. Specific background the phenomenon of flouting these maxims, particularly in film narratives, provides insight into character motivations and interpersonal dynamics. Knowledge gap however, limited research has specifically addressed the instances of maxim flouting by characters in cinematic contexts, particularly in the action-comedy genre, such as in the film Skiptrace. Aims this study aims to analyze the utterances of Connor Watts, a gambler in Skiptrace, focusing on the flouting of conversational maxims and the resulting implicatures. Results the analysis revealed 16 instances of maxim flouting, categorized into four types based on Grice's cooperative principle: quantity, quality, relation, and manner. Novelty this study contributes new insights into the pragmatic functions of flouting maxims in cinematic dialogue, highlighting the nuanced use of language by characters. Implications understanding how Connor Watts employs these conversational strategies not only enhances comprehension of character interactions but also enriches the analysis of communicative practices in film, offering valuable implications for future studies in pragmatics and film discourse. Highlights: Analysis of 16 instances of maxim flouting by Connor Watts. The maxim of quantity was most frequently flouted for manipulation. Insights into character interactions and pragmatic functions in film dialogue. Keywords: Flouting Maxims, Connor Watts, Skiptrace, Implicature, Conversational Analysis